Translating French into French: The case of Close Encounters of the Third Kind - Labate, Simon (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This paper deals with the French dubbed version of Steven Spielberg’s 1977 Close Encounters of the Third Kind. The film features a scientist who mainly speaks French and is helped by an interpreter, who often translates simultaneously or consecutively from French into English and vice versa. In the French dub, however, all the characters speak French, which is why the original redundancy created by the interpreting acts had to be avoided at all cost. The analysis of a number of scenes makes it possible to identify the various translation strategies applied to conceal the original multilingual situations. The textual modifications carried out to produce a coherent French script have repercussions on the image of the scientist and his interpreter as characters in the film.